Dynamics of Union Dissolution in Sub-Saharan Africa - Ben Malinga John; Natalie Nitsche (Population and Development Review, 2022)
Not only whether but also when a union ends and how long individuals remain unpartnered subsequently is consequential for social and demographic outcomes. However, in sub-Saharan Africa (SSA), information about the timing of union dissolution and the reproductive time “lost” due to union dissolution is lacking. We close this gap by applying standard indirect demographic techniques in a novel way to Demographic Health Survey data collected in 34 SSA countries to document (i) the level and timing of all-cause union dissolution and (ii) the time women spend outside of marriage due to union dissolution during their reproductive life course. Results revealed that in 28 out of 34 countries, over one-fifth of first unions end within 15 years, and in 14 out of 34 countries, the proportion of first unions ending within 25 years exceeds 40 percent. The average marital duration at first union dissolution varies between 4.8 and 9.4 years. The pace of remarriage is rapid across all countries, with the average duration between first union dissolution and first remarriage ranging between 0.2 and 2.9 years. The overall reproductive years lost to union dissolution vary between 1.3 and 5.3 years, and account for 4.0–16.3 percent of the total reproductive life expectancy. We discuss the implications of these dynamics for fertility outcomes in SSA.
Keywords: 300; marriage; union dissolution; remarriage; reproductive life expectancy; fertility; sub-Saharan Africa